IoT Prototype in Vertical Parking System for Optimizing Parking Space Management - Aprillia, Rizky; Karna, Nyoman Bogi Aditya; Murti, Muhammad Ary (eProceedings of Engineering, 2024)
As the number of vehicles in major cities like Jakarta increases each year, the availability of parking spaces decreases, causing various problems in economic, social, health, and safety aspects. This study explains the implementation of the Internet of Things (IoT) in a vertical parking model to help optimize parking space. IoT is used to monitor the status of parking slots, whether they are occupied or vacant, and the system can be operated by booking through a website to check available parking slots. Based on test results, the parking lift can lift a 60-gram load to the second floor in 16 seconds and lower the load from the second floor to the first floor in 15 seconds. IoT sensors can detect vehicles in parking slots with a low throughput value of 16.26 bytes/s and 0.00163 kbps. Finally, website testing showed only a delay of 395.8 milliseconds when making reservations. Keywords— Delay, IoT, Lift, Prototype, Parking Lot, Throughput, Website.